A new species of the Lower Ordovician pliomerid trilobite Pseudocybele and its biostratigraphic significance - Mcadams, Neo E. B.; Adrain, Jonathan M. (Zootaxa, 2010)
A low diversity trilobite fauna consisting entirely of new species occurs at several horizons in the Blackhillsian Stage (Floian), in a narrow stratigraphic interval high in the Fillmore Formation in the southern Confusion Range, Ibex area, Millard County, western Utah. This is the type section of the Blackhillsian Stage, the highest of the four stages with comprise the Ibexian Series, the Laurentian Lower Ordovician. The interval occurs between the underlying Presbynileus ibexensis Zone and the overlying "Pseudocybele nasuta Zone". Previous studies assigned the interval to the P. nasuta Zone, but new collections show that the fauna is unique and shares no species with either the underlying or overlying assemblages. It was recognized in 2009 as the Pseudocybele paranasuta Zone, but the name bearer was not formally described. Pseudocybele paranasuta n. sp. is a distinctive pliomerid trilobite with diagnostic features including: clusters of granules on the frontal lobe of the glabella and the middle body of the hypostome; maculae along the lateral branches of the middle furrow of the hypostome; a short, slender median hypostomal spine; and a strong, W-shaped impression in the terminal piece of the pygidium.